Electric vehicle household charging behaviour in Ireland and aims for a carbon neutral electric fleet by 2020. Issue 4 (2015) - Morrissey, Patrick; Weldon, Peter; O'Mahony, Margaret
This paper uses data collected from electric vehicle (EV) household charge points in Ireland to analyse existing EV charging profiles. The potential impacts of increased numbers of EVs in the population on the Irish electrical grid are assessed if EV penetration levels were to increase to different levels in the population. The 2011 census database was used to examine the key demands of the population in terms of their car-based work trips for a number of projected growth scenarios. A large proportion of Irish households were identified as being suitable for the purchase of an EV on this basis. The next step in the research examined the potential impact on the electrical grid of the potential charging demand for the projected scenarios. The projected supply capacity within the Irish electrical grid would appear sufficiently capable to absorb the likely power demand from EVs in both 2016 and 2020 scenarios.